A 3D finite strain viscoelastic constitutive model for thermally induced shape memory polymers based on energy decomposition. (November 2018) - Su, Xiaobin; Peng, Xiongqi
Abstract: A 3D finite strain viscoelastic constitutive model for thermally induced shape memory polymers (SMPs) is proposed in this work. The thermodynamic system of SMPs in the shape memory cycle is decomposed into thermal and mechanical parts, and the two parts are described separately. Then the constitutive equation is derived based on the restrictions of the second law of thermodynamics through a decomposing of the thermodynamic free energy. The concept of phase transition is introduced to greatly facilitate the determination of material parameters, which makes the model easier for application. Three sets of experimental data in the literature are used to validate the proposed model. The simulation results have an excellent consistency with experiment results, which demonstrates the effectiveness of the proposed model in predicting the shape memory effect (SME) of SMPs. Highlights: A 3D finite strain viscoelastic constitutive model for SMPs is proposed. Energy decomposition and phase transition concept are combined for model development. A guideline for material parameter determination is provided.